Модель прийняття адаптивних рішень щодо управління гнучкістю підприємства - Геращенко, Ірина Олексіївна; Мірєйчік, І. А. (Українська державна академія залізничного транспорту, 2013)
В статті викладено сутність управлінського рішення, розглянута та охарактеризована блочна модель підготовки і прийняття адаптивного рішення. Проаналізовані етапи прийняття адаптивного управлінського рішення з урахуванням гнучкості, які представлені у вигляді послідовних етапів, операцій, процедур між якими існують прямі і зворотні зв'язки. Для визначення найбільш обґрунтованого порядку прийняття управлінського рішення, запропонована модель прийняття адаптивного управлінського рішення з урахуванням гнучкості підприємства.

The article describes the nature of the administrative decision, considered and characterized block model preparation and adoption of adaptive solutions. The stages of adaptive management solutions with flexibility, which are presented as a series of steps, operations, procedures, among which there are forward and backward linkages. Revealed that the model management decision involves a movement from one block to another. After discovering the problem, establish the conditions and factors that contribute to its occurrence, developed solutions from which to choose the best. To determine the most reasonable order management decision, a model of adaptive management decision making, taking into account the flexibility of the enterprise. An important factor is the competitive advantage of the enterprise management flexibility, the ability of companies to rapid restructuring of administrative influence, adoption and implementation of adaptive to the current economic circumstances (situations) management solutions for enterprise support of innovative activity and increase its competitiveness.
Adaptive model of decision making on the management of enterprise flexibility
Keywords: управлінські рішення; ефективні рішення; адаптивні рішення; effective solutions; model of adaptive solutions